Anesthesia in Awake Craniotomy Patients - Akim, Mhd; Bisono, Luwih; Hamdi, Tasrif; Sitepu, John Frans; Harahap, Awi Tifani Mayandisa (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Awake craniotomy is a neurosurgical procedure performed while the patient is conscious and cooperative, commonly used to remove brain tumors or epileptic foci located close to brain regions that control in real-time critical functions such as speech, movement, or vision.Case: A 26-year-old male presented to Haji Adam Malik Hospital, Medan with progressive blurred vision in both eyes and headaches over three months diagnosed with secondary headache due to intracranial space-occupying lesions (SOL) (thalamic glioma). The patient was referred to a neurosurgical colleague for further treatment in the form of a craniotomy. The craniotomy was performed using awake anesthesia techniques for the excision of diffuse glioma in the thalamic region. The awake anesthesia technique involved intravenous premedication with 0.25 mg atropine sulfate, 5 mg dexamethasone, 50 mg phenytoin, 2.5 mg diazepam, 100 mcg fentanyl, and dexmedetomidine administered at 20 mcg/hour to achieve the desired sedation level. Prior to incision, infiltration was performed in the area to be incised using 0.75% ropivacaine 20 ml mixed with 2% lidocaine 4 ml, and before the burr hole was made in the cranium, 50 mcg fentanyl was administered intravenously. The surgery proceeded according to protocol, and the patient was transferred to the recovery room.Discussion: Awake craniotomy requires clear communication for brain mapping, making severe aphasia and respiratory disorders like sleep apnea contraindications. Dexmedetomidine is favored for sedation due to its minimal respiratory effects. Local analgesia with ropivacaine and lidocaine ensures pain control and hemodynamic stability, reducing opioid use. The lack of bispectral index monitoring to assess sedation depth is a noted limitation.Conclusion: Considering the benefits and challenges associated with awake surgery, the use of this method should be considered on an individual case basis to ensure surgical success and patient safety.